G362(P) Service redesign in an urgent care department – a multi-disciplinary quality improvement project. (24th May 2017) - Popli, G; Bassett, E; Barnett, N; Edwards, N; Jyothish, D
Abstract : Physical space, manpower and flow constraints adversely affected patient and professional experience in an urgent care floor of a paediatric unit. A structured improvement programme including all members of the wider urgent care team including paediatric trainees, consultants, nurses and managers was undertaken. The first step was to facilitate attendance for the project team at a Quality and Service Improvement and Redesign (QSIR) programme, which provided both clinicians and managers with the analytical tools to understand where to focus their improvement efforts. This resulted in identification of a range of qualitative and quantitative metrics to measure quality of care and experience. Team undertook qualitative surveys of patient and professional experience, quantitative analysis of data including time to definitive care, length of stay as well as governance and adverse events monitoring. Using the above information which identified the barriers to care, a whole system redesign project with multidisciplinary participation was embarked on. The components of the project included implementation of: 1. Guidelines for uniform management of common paediatric conditions across primary and secondary care 2. A GP telephone system with direct access to consultant advice for stream lining of referrals. 3. Rapid access clinics 4. Matching medical and nursing manpower with ebbs and surges in patient flow 5. Improved IT systems for visibility of data and data collection Qualitative and quantitative data collected in the immediate post implementation period demonstrates significant improvements in patient and professional experience as well as reduction in bottlenecks and improved flow on the urgent care floor. Inclusion of key stakeholders and designing collaborative solutions demonstrated resonance with clinical and managerial teams alike in improving patient care and experience. In addition to the objective improvements above, participating paediatric trainees identified this project as enabling them to understand QI methodology, in enabling different professionals to work across professional boundaries in devising lasting solutions which will be key to future projects in quality improvement. Trainee engagement in improving patient care through QI projects will underpin system wide improvements in the future in the NHS.